The Process of Building the Repertory and a Glance to the Roads Ahead: Discussion with Roger Van Zandvoort - Tagori, Yossi (Homœopathic Links, 2018)
This article concerns an interview with Roger van Zandvoort, author of ‘Complete Repertory and Dynamic Repertory’. In some parts, it is referring to an article I published in Vol. 2, 2017, of Homeopathic Link ‘Call for a New Concept of Homeopathic Software’. The parts concerned are those dealing with the future development of the homeopathic software, and especially the possibility to have in future software that will enable colleagues worldwide to share their data and the way these data can contribute to future repertories.
Keywords: Roger van Zandvoort; Complete Repertory; Dynamic Repertory; Symptom's Grading